2022
DOI: 10.1002/oby.23457
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of obesity development in Ceacam1−/− male mice by bone marrow transplantation or introduction of the human CEACAM1 gene

Abstract: ObjectiveAlthough Ceacam1−/− male mice become obese on normal chow, the effect of bone marrow transplantation or introduction of the carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) gene has not been studied, to the knowledge of the authors.MethodsThis study analyzed Ceacam1−/− mice on normal diet or high‐fat diet (HFD), including effects of bone marrow transplantation or introduction of the CEACAM1 gene.ResultsMale Ceacam1−/− mice on normal diet versus HFD for 24 weeks gained significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[ 196 ] The expression of FGF21 in this group, along with a ≈5‐fold increase in CEACAM1 expression, is likely significantly associated with the increase in bone marrow adiposity and whole‐body weight gain measured in this group. [ 197 ] Estrogen has been shown to reduce adipogenesis through the direct inhibition of PPARγ, [ 198–201 ] however, our in vitro investigations reveal no P7C3‐induced reduction in this major adipogenic regulatory gene, suggesting the induction of an alternative adipogenic route. Insulin receptor was also upregulated by P7C3.…”
Section: Discussionmentioning
confidence: 78%
“…[ 196 ] The expression of FGF21 in this group, along with a ≈5‐fold increase in CEACAM1 expression, is likely significantly associated with the increase in bone marrow adiposity and whole‐body weight gain measured in this group. [ 197 ] Estrogen has been shown to reduce adipogenesis through the direct inhibition of PPARγ, [ 198–201 ] however, our in vitro investigations reveal no P7C3‐induced reduction in this major adipogenic regulatory gene, suggesting the induction of an alternative adipogenic route. Insulin receptor was also upregulated by P7C3.…”
Section: Discussionmentioning
confidence: 78%
“…In this respect, we have recently shown that human CEACAM1 directly associates with the fatty acid uptake receptor CD36 in human HepG2 hepatocytes [21] and is phosphorylated by a combination of protein kinase A (PKA) and glycogen synthase kinase 3b (GSK3b) [22]-key kinases that regulate glucagon [23] and insulin signaling [24,25]. In addition, the deletion of CEACAM1 in mice leads to an elevation of CD36 and pAMPK expression [26]-proteins that are co-regulated in skeletal and heart muscle [27]. In terms of CVD, endocardiography revealed increased septal wall thickness in male Ceacam1 −/− mice but not in CEACAM1 liver-reconstituted male Ceacam1 −/− mice [19].…”
Section: Introductionmentioning
confidence: 99%